Advances in Fruit and Vegetable Quality, Bioactive Compounds, and Nutritional Value: 2nd Edition - Andrea Gómez-Zavaglia; Lucía Cassani (Foods)
In recent years, substantial progress has been made in characterizing the quality of fruits and vegetables, identifying bioactive compounds, and developing novel food matrices with enhanced nutritional value [...]